30-50 day oscillation of monsoon: Some Simple mechanisms (MAUSAM, 1990)
Morphology of jO-50 day oscillation found in summer monsoon in different directions, different weather parameters and at various levels has been discussed. Model studies of these oscillations and their northward movement In the Indian region are described in this paper by a system of equations and their solutions.